THE EFFECT OF PRIVATE LABEL, SERVICE QUALITY, PRODUCT DISPLAY AND PRICE DISCOUNT ON IMPULSE BUYING AT PT. X MABAR HILIR BRANCH, MEDAN CITY - Tiza Rahmadina; Sugih Arto Pujangkoro; Syafrizal Helmi Situmorang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Supermarket or minimarket sales are carried out impulsively (Impulse Buying). In this study, impulse purchases are thought to be influenced by four factors, namely private labeling, service quality, product displays, and price discounts. For this reason, the researcher explains how the challenges of this research are formulated: 1) Does private label affect impulse purchases at PT. X Mabar Hilir Branch? 2) Does the quality of service affect impulse purchases at PT. X Mabar Hilir Branch? 3) Does the product display have an impact on impulse buying at the PT. X Mabar Hilir Branch? 4) Does the price cut have an impact on impulse purchases at PT. X Mabar Hilir Branch?; How to do Private Label, Service Quality, Product Display, & Price Discount All Affect Impulse Buying at the PT. X Mabar Hilir Branch? In this study, 150 PT. X Mabar Hilir clients served as the quantitative research samples. The study's findings are as follows: (1) Private Label has a positive and significant impact on customers' impulsive purchases during PT. X Mabar Hilir with t counts > the ttable (2.501 > 1.97646), and the significance of t is below 0.05 (0.013 0.05); (2) Service Quality has a positive as well as a significant impact on customers' impulsive purchases that PT. X Mabar Hilir with t counts > the ttable (2.375 > 1.97646); (3) Price has a positive and significant; (3) Through tcount > ttable (2.501 > 1.97646) and the significance of t is below 0.05 (0.013 0.05), product display has an important and beneficial effect on consumer impulse buying at the PT. X Mabar Hilir Branch; Price discounts have a positive and significant impact on consumer impulse purchases at PT. X when tcount > ttable (2.011 > 1.97646) as well as the significance of t is less than 0.05 (0.046 0.05); ((5) For f counts > ftable (59.565 > 2.43) or an importance of 0.05, private label, service quality, product display, and price discount have a positive and significant impact on consumer impulse buying at PT. X. Branch Mabar Hilir .